Quality Control Tests in Some Diagnostic X-Ray Units in Bangladesh - Begum, M; Mollah, AS; Zaman, MA; Rahman, AKMM (Bangladesh Journal of Medical Physics, 2013)
Regular implementation of quality control in diagnostic x-ray facilities is essential to provide good quality images which lead to proper diagnoses with minimum hazard and distress. Important performance tests in diagnostic radiology in Bangladesh are carried out according to a quality control protocol and the measured parameter values are compared to the relevant acceptance limits. In this work, beam alignment, field congruence, nominal focal spot, film-screen contact and half value layer for diagnostic x-ray facilities are measured by using beam alignment test tool, RMI/Victoreen collimator test tool, Bar pattern focal spot test tool, film/screen contact test tool (RMI143D), Gammex RMI step wedge and densitometer from forty different diagnostic x-ray facilities in Bangladesh. For congruence between optical and radiation fields, 77.5% are found to be within limit and 60% of facilities are within the beam alignment limit. For most of the installations, 92.5% nominal focal spot size of diagnostic x-ray machines is matched perfectly with the rating of focal spot size. In an effort to improve image quality, this study has checked the film-screen contacts of multiple facilities and found 65% to have the expected uniformity. While investigating half value layers (HVL), a measure of x-ray beam quality, it is found that none of the diagnostic x-ray installations can achieve the recommended levels. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14688 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 59-66